PM2.5 arising from different cooking fuels in rural residential houses - Amant, H.; Ali, Z.; Sidra, S.; Nasir, Zaheer A.; Colbeck, Ian (Pakistan Agricultural Scientists Forum, 2015)
A study was conducted in the rural area of Kasur district, Pakistan to monitor PM2.5levels generated by different fuel types. Three rural houses were selected, one burning wood as primary cooking fuel while the other two employed LPG for cooking purposes. Burning of wood caused PM levels to increase 37 times above the WHO recommended limit of 25 µg/m³ while smoking also contributed significantly increasing PM levels up to 48 times than the recommended limit. LPG was observed to increase the levels up to 14 times. It is important to promote the use of cleaner fuels as increased exposure to PM levels generated by biomass fuel burning can have a significant impact upon human health.
Keywords: particulate matter; biomass fuels; LPG; rural houses; Pakistan